Design of Biorefineries for High Value Added Products from Fruits (2015)
This research was aimed to evaluate the design of biorefineries from fruits and its wastes. Valuable compounds such as ethanol, xylitol, oil and extracts containing phenolic compounds with antioxidant capacity were obtained using the biorefinery concept. For this purpose, two feedstocks were used, Spent Blackberry Pulp (SBP) (Rubus glaucus benth) and avocado (Persea Americana mill). Additionally, two cases of studies were evaluated, naranjilla waste (Solanum quitoense) and Spent Coffee Grounds SCG. Both, SBP and avocado were chemically characterized found its content of cellulose, hemicellulose, lignin, ash, extractives and valuable compounds such as phenolic compounds and oil. Four biorefineries were designed and evaluated using SBP, avocado, naranjilla waste and SCG for obtaining value added products. and two cases studies. Techno-economic and environmental assessments were developed to the proposed biorefineries. Finally, the results and analyses made allow giving a biorefinery approach based on fruits and its wastes